2003
DOI: 10.1002/zaac.200390143
|View full text |Cite
|
Sign up to set email alerts
|

On the Donor Ability of the Phosphaneiminato Substituent and Cube Formation with Transition Metal Fragments

Abstract: The particular role of the phosphaneiminato ligand as a donor is investigated for a) nitrenes (phosphinidenes) and carbenes and b) cubane formation with transition metals. Accordingly, and as shown for the case a) the ligand is a stronger π‐donor than an amino group and can be considered as a special case of imine‐type substituents. The latter are very effective in π‐donation. In the case b), i.e. the cubane formation with transition metals, one has to consider transition metals with a partially or completely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Although tables of substituent constants27, 28 indicate that amino groups are the premier π‐donor groups, we were aware of some theoretical and experimental evidence that N‐bound iminophosphorano groups (R 3 P=N)2933 should be regarded as stronger electron‐donating substituents. Indeed, calculations by Schoeller have shown a greater stabilization of the singlet state of the corresponding phosphanylnitrenes (R 2 PN) for R=H 3 P=N over R=H 2 N 34. 35 In addition, whereas diaminochloroboranes [(R 2 N) 2 BCl] are covalent species with discrete BCl bonds,36 the isolation of the chloride salt of a dicoordinate borinium cation [ t Bu 3 P=N) 2 B][Cl] by Stephan et al 29.…”
Section: Methodsmentioning
confidence: 99%
“…Although tables of substituent constants27, 28 indicate that amino groups are the premier π‐donor groups, we were aware of some theoretical and experimental evidence that N‐bound iminophosphorano groups (R 3 P=N)2933 should be regarded as stronger electron‐donating substituents. Indeed, calculations by Schoeller have shown a greater stabilization of the singlet state of the corresponding phosphanylnitrenes (R 2 PN) for R=H 3 P=N over R=H 2 N 34. 35 In addition, whereas diaminochloroboranes [(R 2 N) 2 BCl] are covalent species with discrete BCl bonds,36 the isolation of the chloride salt of a dicoordinate borinium cation [ t Bu 3 P=N) 2 B][Cl] by Stephan et al 29.…”
Section: Methodsmentioning
confidence: 99%
“…Such compounds are subject to circumambulatory (walk) rearrangement caused by rapid migration of substituents, which make them particularly interesting. [13][14][15][16] This unique fluxional phenomenon is in many cases easily observed by NMR spectroscopy via the temperature dependence of chemical shifts. [17][18][19][20] Numerous 5-substituted 1,3-cyclopentadienyl derivatives have therefore been prepared to study this effect.…”
Section: Introductionmentioning
confidence: 96%
“…[17][18][19][20] Numerous 5-substituted 1,3-cyclopentadienyl derivatives have therefore been prepared to study this effect. Experimental and theoretical investigations of circumambulatory behavior have been reported for silicon, 19,[21][22][23] germanium, 19,[23][24][25] phosphorus, [13][14][15][16]26 and arsenic 27,28 derivatives. The title compound, which was recently synthesized, 13 has also been the subject of such an investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The circumambulatory rearrangement easily observed by NMR spectroscopy for numerous derivatives leads to signals at chemical shifts dependent on the temperature and the nature of the substituents . Numerous experimental studies and theoretical calculations have been reported on silicon, germanium, , phosphorus, , or arsenic derivatives. , …”
Section: Introductionmentioning
confidence: 99%